1996
DOI: 10.1177/146642409611600408
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health status of sawmill workers in Nigeria

Abstract: The health impact of exposure to sawdusts on 59 sawmill workers from southwest Nigeria was studied. Workers were chosen by a two-stage random sampling method from 15 privately owned sawmills. Peak flow and spirometric measurements were obtained from all workers. They also underwent a structured questionnaire which elicited occupationally related symptoms. Age and sex matched controls consisting of 199 workers from similar socio-economic backgrounds as the subjects underwent similar questionnaire and lung funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
8
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 6 publications
1
12
8
2
Order By: Relevance
“…12 Fatusi et al, found that the sawmill workers had significant lower lung function indices (FVC, FEV1 and PEFR) compared to the control group. 13 The mean observed values of pulmonary function test indices in cases and controls obtained by us are slightly on lower side than the mean values obtained by Fatusi et al 13 Meo et al, observed that there was a significant reduction in the mean values of Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), and Maximum Voluntary Ventilation (MVV) in wood workers relative to their matched controls. This impairment was increased with the duration of exposure to wood industries.…”
Section: Discussioncontrasting
confidence: 49%
“…12 Fatusi et al, found that the sawmill workers had significant lower lung function indices (FVC, FEV1 and PEFR) compared to the control group. 13 The mean observed values of pulmonary function test indices in cases and controls obtained by us are slightly on lower side than the mean values obtained by Fatusi et al 13 Meo et al, observed that there was a significant reduction in the mean values of Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), and Maximum Voluntary Ventilation (MVV) in wood workers relative to their matched controls. This impairment was increased with the duration of exposure to wood industries.…”
Section: Discussioncontrasting
confidence: 49%
“…More recently, asthma, COPD, chronic cough and/or rhinitis induced by occupational exposure have been identified in developing countries (591,(624)(625)(626)(627)(628)(629)(630)(631)(632)(633)(634)(635)(636)(637)(638).…”
Section: Other Mitesmentioning
confidence: 99%
“…Respiratory impairment: Rural and urban areas of Africa where industries are situated have been shown to have a high prevalence of respiratory symptoms and reduced lung function. For example, this author demonstrated a high frequency of occurrence of cough alone, cough with sputum, morning phlegm, nasal catarrh, chest pain and reduced lung function among the residents of Bacita, Kwara State, Nigeria sequel to their exposure to air pollution from the process of sugar production(1) and Fatusi et al (17) also drew similar conclusions from sawmill workers in southwest Nigeria. In eastern Africa, Mengesha et al (2) studying the respiratory effects of dust in different sections of yarn, cement and cigarette factories found a higher prevalence of chronic cough, chronic bronchitis and bronchial asthma among the workers than the controls.…”
Section: Introductionmentioning
confidence: 78%